2010
DOI: 10.3354/cr00896
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in heat resistance and HSP70 expression in inbred isofemale lines of the springtail Orchesella cincta

Abstract: The functional relationship between thermotolerance and heat shock protein (HSP) expression is well described. However, the intraspecific variation in HSP70 expression and heat resistance is not fully understood. Some studies have shown a correlation between thermotolerance and HSP70 expression levels at the intraspecific level, whereas others have not, and results depend on species, developmental stage and environment. The present study extends such correlative studies to species from soil ecosystems, where w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Several studies have found a positive correlation between heat tolerance and HSP70 expression (Bahrndorff et al, 2009), whereas others have shown opposite or no correlations (Dahlgaard et al, 1998;Bahrndorff et al, 2009Bahrndorff et al, , 2010. Using the same treatments as herein a previous study on B. anynana, we showed that exposure for 2 h to 39 1C strongly increased subsequent heat-stress survival (Franke and Fischer, 2013), suggesting that a positive relationship between HSP70 expression and heat tolerance exists also in our study organism.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Several studies have found a positive correlation between heat tolerance and HSP70 expression (Bahrndorff et al, 2009), whereas others have shown opposite or no correlations (Dahlgaard et al, 1998;Bahrndorff et al, 2009Bahrndorff et al, , 2010. Using the same treatments as herein a previous study on B. anynana, we showed that exposure for 2 h to 39 1C strongly increased subsequent heat-stress survival (Franke and Fischer, 2013), suggesting that a positive relationship between HSP70 expression and heat tolerance exists also in our study organism.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, some studies have documented increased HSP70 expression following inbreeding, which has been interpreted as part of a more general stress response which may include even 'genetic stress' caused by inbreeding (Kristensen et al, 2002;Cheng et al, 2006;but Bahrndorff et al, 2010). However, a higher HSP70 expression in inbred compared with outbred Drosophila larvae were only found at less stressful intermediate temperatures, whereas they disappeared under more stressful conditions (Kristensen et al, 2002;Cheng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous population- or line-specific analyses of Hsp70 expression levels in other invertebrates clearly demonstrated within and among population differences in Hsp70 levels [22][24]. However, the specific demographic parameters responsible for the correlation of population structure and Hsp70 levels are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…First, there was no correlation between the level of inbreeding and the trait values for any of the three life-history traits considered in this study, while inbreeding is known to cause deleterious effects on several life-history parameters (DeRose and Roff 1999). Second, a previous study with these lines also showed no change in a stress resistance nor heat shock protein (Hsp70) induction (Bahrndorff et al 2010), traits usually associated with inbreeding depression (Kristensen et al 2002). The relative lack of inbreeding effects may be due to the slow rate of inbreeding, as minimal population size was never smaller than five individuals.…”
Section: Positive Effects Of Genotypic Richnessmentioning
confidence: 94%